2021
DOI: 10.1007/s00011-021-01476-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute reduction of visual acuity and visual field after Pfizer-BioNTech COVID-19 vaccine 2nd dose: a case report

Abstract: Long-term and rare adverse effects of COVID-19 vaccines are unknown. Hence, it is important to report them to improve the safety profile of the vaccines and enhance their use worldwide. Here, we describes a case of acute visual impairment after Pfizer-BioNTech vaccine second dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 7 publications
1
23
0
Order By: Relevance
“…Santovito and Pinna previously reported on a male patient who developed sudden darkening of his visual field after receiving the BNT162b2 vaccine but were unable to comment on an etiology [133]. We have previously discussed this case elsewhere, suggesting that it may have been an optic neuropathy [14].…”
Section: Other Reportsmentioning
confidence: 88%
“…Santovito and Pinna previously reported on a male patient who developed sudden darkening of his visual field after receiving the BNT162b2 vaccine but were unable to comment on an etiology [133]. We have previously discussed this case elsewhere, suggesting that it may have been an optic neuropathy [14].…”
Section: Other Reportsmentioning
confidence: 88%
“…His symptoms got relieved after taking analgesics. Possibly, patient had an acute attack of migraine with aura that got precipitated by the vaccine [ 106 ].…”
Section: Other Cranial Nerve Involvementmentioning
confidence: 99%
“…Santovito et al reported that a middle-aged, previously healthy male developed a sudden onset of darkening of the visual field three days after receiving the second dose of BNT162b2 COVID-19 vaccine. He also developed light confusion, asthenia, and profound nausea [39].…”
Section: Other Reports With Only Ocular Symptoms Mentionedmentioning
confidence: 99%